Penggunaan Metode Preference Selection Index (PSI) Untuk Penentuan Kondisi Laser Cutting - Yaslinda Lizar; Alya Sahira Firrizqi (JOSTECH Journal of Science and Technology, 2023)
This study discusses the application of the Preference Selection Index (PSI) method or Preference Selection Index to be able to optimize laser cutting. The application of the PSI method represents the decision making of a multi-criteria MCDM that has not been studied more and requires a consideration in determining laser cutting parameters. The main purpose of applying this method is for multi-criterion decision making (MCDM) that does not require an assessment of the relative significance of the criteria under consideration. The method used is the preference selection index, which can provide convenience in making decisions because the process is very simple. The results of experiments using the L27 Taguchi orthogonal array, Cut surface roughness, heat-affected zone (HAZ), kerf width and material removal rate (MRR) were considered optimization criteria. The methodology is found to be particularly useful in real manufacturing environments as it involves simple calculations that are easy to understand and apply.